Periprosthetic humeral fractures after shoulder arthroplasty - Anna Behrens; Nick Moronga; Milad Farkhondeh Fal; Konrad Mader; Lukas Heilmann; Till Orla Klatte (EFORT Open Reviews)
Occurring in 0.5–3% of cases, periprosthetic humerus fractures pose a challenge, necessitating effective management strategies. A comprehensive review was conducted using PubMed. Used terms included ‘Periprosthetic humerus fractures; complications; periprosthetic fractures shoulder arthroplasty; periprosthetic humeral fracture treatment; nerve palsy humeral revision arthroplasty; infections after shoulder arthroplasty; postoperative complications AND open reduction AND humeral fractures; allograft AND long humeral stem’. Studies were excluded if they did not meet the actual topic, included more than primary shoulder arthroplasty and/or were in non-English or non-German language. Thirty-eight papers with evidence levels ranging from two to three were selected for this review. Various classification systems have been implemented; their validation though was based on studies with only a limited number of patients. Risk factors include osteopenia/osteoporosis, rheumatoid arthritis, age, age-related lifestyle and gender. Treatment options range from conservative approaches to plate osteosynthesis or revision to a longer stem. Nevertheless, there is a lack of biomechanic studies and randomized-controlled clinical studies; hence, the evidence is low. Complications in revision arthroplasty encompass infections, nonunions, and nerve palsies, highlighting the importance of individualized treatment planning. The management of periprosthetic humeral fractures requires careful consideration of risk factors and tailored treatment plans. Existing literature relies on small case series and expert opinions, highlighting the need for further research to establish optimal treatment strategies for these challenging fractures.